A STUDY ON DEPLOYMENT OF DIFFERENTLY-ABLED PERSONS IN INDIAN HOSPITALITY INDUSTRY IN PURVIEW OF SERVQUAL MODEL (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
The consumer is a crucial factor in the  promotion of any business. This paper is about  consumers’ perception and intention on the  deployment of differently-abled persons (DAP)  in the Indian hospitality industry. The modified  SERVQUAL model was used to study the  consumers’ concern about accepting the services  of DAP in the hospitality sector. Data was  collected through a structured questionnaire  in Google form among consumers all over  the country, which was measured on a five point Likert scale to find out their choice of  the inclusive Indian hospitality industry. A  quantitative analysis reveals that consumers  all over India have a positive attitude towards  DAP staff, but neither they assuring of return  business nor are they empathetic towards them.  This work identified that the management of  such organizations needs to be more strategic  and adaptable. This paper represents original  research that encourages hospitality businesses  to employ DAP.
Keywords: SERVQUAL; RPWD; Consumer satisfaction